Conservative Treatment of a Large Facial Midroot Perforation - Stephane Kerner; François Bronnec (Case Reports in Dentistry)
Aim. To report on the endodontic and periodontal management of a root and alveolar process perforation in a maxillary front tooth. Summary. Perforation during access cavity preparation is an infrequent complication during endodontic therapy, leading to potential periodontal tissue breakdown. The case described the two-stage management of a massive facial root perforation requiring a connective tissue graft to correct a mucosal fenestration persisting after orthograde repair of the root defect with MTA.